Synthesis and biological evaluations of new phenothiazine derivatives - Irhaeem kadhim, Muqdad (Al-Qadisiyah Journal of Pure Science, 2018)
This work includes synthesis of new derivative of phenothiazine , in order to obtain these derivatives ; chalcone 3 was subjected to a Aldol condensation reaction between 10-ethyl-3- phenothiazin-3-yl carbaldehyde , this compound was reacted with some different reagent such as hydrazine hydrate , phenyl hydrazine , thiosemicarbazide and hydroxyl amine to give pyrazolines 5,6,7,8 and oxazoline 9 . The structures of all the compounds were confirmed by microanalyses and various spectral data . the synthesized new compound were screened against antimicrobial activity .